Shamanizm or Tengrian? - Жеңіс, Ж Ж (Journal of Oriental Studies, 2016)
In modern scientific environment traditional world out-look of turks is called “shamanizm”, under the name of the religious representative. This obvious distortion of the name, as well as earlier, the Europeans named islam as “magoumetin” or “busurmanian”. Actually, shamanizm to the attitude to shaman not religion, and only activity of the separate persons, which has the special quality. Owning in the special quality shaman was engaged by treatment, prediction or indication of miracles. Thus shamans have realize